2010
DOI: 10.1111/j.1476-5381.2010.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microsomal prostaglandin E2 synthase‐1 as a molecular basis for the anti‐inflammatory actions of boswellic acids from frankincense

Abstract: BACKGROUND AND PURPOSEFrankincense, the gum resin derived from Boswellia species, showed anti-inflammatory efficacy in animal models and in pilot clinical studies. Boswellic acids (BAs) are assumed to be responsible for these effects but their anti-inflammatory efficacy in vivo and their molecular modes of action are incompletely understood. EXPERIMENTAL APPROACHA protein fishing approach using immobilized BA and surface plasmon resonance (SPR) spectroscopy were used to reveal microsomal prostaglandin E2 synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 44 publications
1
85
0
Order By: Relevance
“…mPGES-1 as target of these NPs may provide a basis for their antiinflammatory properties and rationalize their use in folk medicine as remedy for treatment of inflammatory disorders. Among these plant-derived mPGES-1 inhibitors are prominent antiinflammatory and anti-tumoral compounds like the polyphenol curcumin from turmeric [86], epigallocatechin-3-gallate (EGCG) from green tea [87], the acylphloroglucinol hyperforin from St. John´s wort [66] and garcinol from Garcinia indica [88], triterpene acids from frankincense (e.g., tirucallic acids, lupeolic acids, boswellic acids,) [89,90], the diterpenoids carnosol and carnosic acid from Salvia officinalis [91], and the quinone embelin from Embelia ribes [92]. All of them inhibit mPGES-1 in cell-free assays in the submicromolar range (Table 1).…”
Section: Inhibitors Have Been Reported Yetmentioning
confidence: 99%
“…mPGES-1 as target of these NPs may provide a basis for their antiinflammatory properties and rationalize their use in folk medicine as remedy for treatment of inflammatory disorders. Among these plant-derived mPGES-1 inhibitors are prominent antiinflammatory and anti-tumoral compounds like the polyphenol curcumin from turmeric [86], epigallocatechin-3-gallate (EGCG) from green tea [87], the acylphloroglucinol hyperforin from St. John´s wort [66] and garcinol from Garcinia indica [88], triterpene acids from frankincense (e.g., tirucallic acids, lupeolic acids, boswellic acids,) [89,90], the diterpenoids carnosol and carnosic acid from Salvia officinalis [91], and the quinone embelin from Embelia ribes [92]. All of them inhibit mPGES-1 in cell-free assays in the submicromolar range (Table 1).…”
Section: Inhibitors Have Been Reported Yetmentioning
confidence: 99%
“…1). Whereas in the past the anti-inflammatory effects were mainly attributed to the inhibition of 5-LO by AKBA [11], recent research revealed the relevance of the whole fraction of triterpenoid acids and the involvement of much more molecular targets than only 5-LO, especially catG and mPGES-1 [9,[12][13][14][15]. Commercially available frankincense consists of the oleo gum resin obtained from trees of Boswellia serrata Roxb.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Earlier studies have suggested that both KBA and AKBA interfere with production of leukotrienes by inhibition 5-lipoxygenase; however, more recent research has shown that other BAs specially b-boswellic acid also play an important role, targeting the microsomal prostaglandin (PG) E2 synthase-1 (mPGES-1) as well as cathepsin G (CatG) thereby complementing the inflammatory action of KBA and AKBA (Tausch et al, 2009;Abdel et al, 2011;Siemoneit et al, 2011;Skarke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%